Effects of different frequencies of whole body vibration on muscular performance - da Silva, M. E.; Nunez, V. M.; Vaamonde, D.; Fernandez, J. M.; Poblador, S.; Garcia-Manso, J. M.; Lancho, J. L. (Biology of Sport, 2006)
The effects of different frequencies (20, 30, and 40Hz) of whole body Vibration were analyzed in order to detetrnine which one of them is the most effective for muscular performance training. Thirty-one subjects participated in the study maintaining their regular exercise habits but avoiding any strength or Jump training. All subjects underwent exposure to the three frequencies with all the other Vibration training variables remaining unchanged: the application order was assigned randomly. The vertical sinusoidal Vibration protocol consisted of 6 exposures of 60s duration each, with 2-min rests in between. The tests used for assessment of muscular performance were the following: 1RM, SJ, CMJ, and muscle power. The performed tests showed increase for the 20- and 30Hz frequencies, being greater the increases for the 30Hz frequency for Sj (p<0.001), CMJ (p<0.01), and power (p<0.001): strength values, on the contrary, did not show any significant changes for any of the frequencies. In contrast, the 40Hz frequency had a tendency to decrease the values in all the analyzed parameters. It can be derived that. when applied to physically active subjects. the 30Hz frequency is the most ideal for eliciting improvement in neuromuscular behavior with whole body Vibration training.